In-plane seismic response of rubble stone masonry specimens by means of static cyclic tests. (1st May 2015) - Milosevic, Jelena; Lopes, Mário; Gago, António Sousa; Bento, Rita
Highlights: Characterization of mechanical behavior of the traditional rubble stone masonry. Experimental evaluation of displacement and strength capacity via static cyclic test. Analysis of the cyclic stiffness degradation, energy dissipation and viscous damping. Abstract: In several seismic countries, unreinforced masonry buildings are still used as residential buildings. Despite their popularity, there is a general lack of knowledge concerning the seismic behavior of such buildings. For this reason, a research programme was initiated in the framework of the SEVERES project to contribute to the understanding of the seismic behavior of such structures. In this campaign, four rubble stone masonry specimens typical of Lisbon old buildings were tested. This was done by applying static cyclic horizontal loads on top, combined with a pre-compression level, to obtain information about the failure mode, maximum displacement capacity and strength capacity. Furthermore, other features of cyclic behavior of the specimens relevant for their seismic performance, i.e., cyclic stiffness degradation, energy dissipation and viscous damping, were also analyzed and discussed.